Legal Definitions and Types of Found Goods In Fiqh Muamalah - Rismayanti, Rini; Desy Dahliani Fadilah; Deni Maulana (Program Studi Ekonomi Syariah, 2024)
Found item isn't specific term for a particular type of property; it is a general term. Luqathah is an item that found at a public area. Taking luqathah is obligatory according Shafi'i Madhhab for saving the property of fellow Moeslim but it have to announced for a year. However, taking luqathah according Maliki Madhhab is makrooh because it is feared that there maybe negligence in matters there are required, such as announcing the found item to the public. Shafi'i Madhhab and Maliki Madhhab have the difference opinion about luqathah. Therefor, the purpose of this study is to find out what should the finder of found item do and what theese two madhhab think about the ownership of found item. Imam Malik and Imam Shafi'i both allow to use of luqathah. According to Imam Maliki, the announcement must be made if there are no people take the luqathah as long as a year. The finder of luqathah have a responsibilty to compensate the item that used or donated. Shafi'i and Malik agree if the luqathah is priceless or doesn't have any valuable that no need to saved, but it must be saved and announced if the item has valuable so its owner known.